Establishment of the relationship between tumor size and range of histological involvement to evaluate the rationality of current retinoblastoma management. - Jianhua Yan (Public Library of Science (PLoS), 2013)
Purpose To determine whether tumor size correlates with histopathological involvement and hence evaluate the rationality of conservative treatment for retinoblastoma. Methods We retrospectively studied 221 patients (221 eyes) treated for retinoblastoma with enucleation in the Zhongshan Ophthalmic Center of Sun Yat-sen University, China, from October 1995 to December 2004. Histopathological data included involvement of the anterior chamber, sclera, choroids, and optic nerve. Tumor size was measured by B-ultrasound examination. Results Tumor invasion of the optic nerve correlated with the Reese-Ellsworth (R-E) staging system and the International Classification for Retinoblastoma (ICRB): optic nerve involvement was significantly more frequent in R-E stage V (P = 0.009) and ICRB Group E (P = 0.002) cases. However, 19.1% of patients with R-E stage I, II and III, and 16.7% of patients with ICRB Group B and C disease showed histopathological involvement of the postlaminar optic nerve. Extraocular involvement was observed in 17.7% of tumors ≤ 15 mm in diameter. Tumors >15 mm in diameter showed greater extraocular involvement, including the optic nerve (P = 0.000) and sclera (P = 0.032), than tumors ≤ 15 mm in diameter. Postlaminar optic nerve invasion was observed in 19.6% of tumors ≤ 10 mm in thickness. Tumors >10 mm in thickness had sclera involvement more frequently than tumors ≤ 10 mm in thickness (P = 0.029). Postlaminar optic nerve invasion was noted in 17.1% of patients with tumors ≤ 15 mm in diameter and ≤ 10 mm in thickness. Conclusions Medium-sized retinoblastomas frequently invade outside the globe. Thus, indications for conservative treatment need improvement.